What drives an amyloid protein precursor from an amyloidogenic to a native-like aggregation pathway? - Quintas, Alexandre (2013)
Conformational disorders such as Alzheimer’s, Parkinson’s, familial amyloidotic polyneuropathy and spongiform encephalopaties are a consequence of protein misfolding and aggregation predominantly in the form of amyloid fibrils. These pathologies represent a major health problem, which most probably will overwhelm the health systems of developed countries in the near future. Significant progress has been made recently to understanding the underlying mechanism of protein misfolding and aggregation. The current picture of protein aggregation is a phenomenon resulting from protein conformational fluctuations leading to misfolded intermediates prone to form non-native interactions with other intermediates, resulting in amyloid fibril formation. Fortunately just a small group of proteins are associated with human conformational disorders. The primary causes that lead this group of proteins to misfolding and aggregation are point mutations, protein over-expression and failure of protein quality-control system. Beside amyloid formation, there are other types of aggregation available to a misfold-disease-related polypeptide chain in the proteinfree energy landscape. Among them, native-like aggregation is becoming a widely studied topic of research.